Islamisasi dan Transformasi Sosial di Tatar Sunda pada Periode 1900-1942 - Supendi, Usman; Hambaliana, Dandie (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The phenomenon of Islamization and social transformation that took place in Tatar Sunda between 1900 and 1942, a period that encompassed the Dutch colonial period and significant social changes in Sundanese society. Islam, which had entered the region since the 15th century, experienced rapid development in the early 20th century, especially amidst the political, social and cultural dynamics taking place in West Java. This study aims to explore the role of Islam in changing the social structure, as well as the interaction between religion, politics and economics in Sundanese society during this period. Using a historical and sociological approach, this article analyses the various factors that drove the Islamization process in Sundanese Tatar, including the role of local ulama, Islamic boarding schools, as well as Islam's involvement in the independence movement. In addition, the article also highlights how this Islamization process contributed to social transformations, such as changes in the education system, relations between social classes, and forms of resistance to Dutch colonialism. The results show that although the Islamization process did not take place in a homogeneous manner, Islam succeeded in shaping a more cohesive social identity of Sundanese society. Pesantren and the ulama network became the center of the spread of Islamic teachings that not only influenced religious practices, but also had an impact on the formation of the socio-political consciousness of the community. Overall, the 1900-1942 period was an important moment in shaping the character of Islam in Sundanese Tatar, which contributed to the resistance against colonialism and the formation of Indonesian nationalism.